Copper(II)-Mediated Cascade Oxidative C–C Coupling and Aromatization: Synthesis of 3-Hydroxyphenanthridinone Derivatives - Yu, Qingzhen; Zhang, Nan; Tang, Yang; Lu, Hang; Huang, Jianhui; Wang, Songqing; Du, Yunfei; Zhao, Kang (Synthesis, 2012)
A novel copper(II) acetate mediated synthesis of 3-hydroxyphenanthridin-6(5H)-ones from N-(3-oxocyclohex-1-enyl)benzamides was developed. The process is postulated to involve an intramolecular oxidative C(sp2)–C(sp3) bond formation followed by dehydrogenative aromatization.
Keywords: copper(II) acetate; phenanthridinone; C–H functionalization; C–C oxidative coupling; dehydrogenative aromatization